Conceptualizing the Practical Knowledge of Survival - Boa Sorte, Paulo (The ESPecialist, 2015)
This paper explores the notion of Practical Knowledge of Survival from the combination of the concepts of knowledge (Geertz, 1983/2009; Tardif, 2002) with the survival strategies theory (Woods, 1990). Initially, we discuss the theoretical perspectives on knowledge. In this discussion, we indicate how they can engage in a conversation with Woods’ survival strategies (1990). Then, we identify, through semi-structured interviews (Lüdke & André, 1986; Rizzini, 1999), the Practical Knowledge of Survival in English language teacher education, informed by experienced teachers enrolled in an English Language Teaching undergraduate program. The results show the various ways of dealing with the adversities that arise in the daily routine of the English language teaching profession.